Robust power allocation for orthogonal frequency division multiplexing-based overlay/underlay cognitive radio network under spectrum sensing errors and channel uncertainties - Zhu, Ling; Zhao, Xiaohui (IET communications, 2016)
In this study, a robust power allocation scheme with orthogonal frequency division multiplexing-based cognitive radio network is proposed to maximise total data transmission rate subject to interference power constraint of primary user (PU) and transmit power budget constraint of secondary user where channel uncertainties and spectrum sensing errors are simultaneously considered. The authors first formulate the interference model by taking the imperfect spectrum sensing into account, then the channel state information errors are considered and assumed to be bounded with ellipsoidal and interval sets to establish robust resource allocation problem. On the basis of the worst-case approach and Lagrange dual decomposition method, the original optimisation problem is converted into a convex one and solved. Simulation results show the robustness of their proposed scheme and the trade-off performance with a sub-optimal data transmission rate, but better protection of PU.